Pengaruh keharmonisan keluarga terhadap perilaku seksual pranikah pada remaja - Lydia Nur Ari Rachmawati; Agustin Rahmawati; Ritna Sandri (Jurnal Psikologi Tabularasa, 2020)
Premarital sexual behavior is all behavior that comes from within a person or outside himself because it is driven by sexual desire that is carried out on or with his sexual object, where the sexual behavior is carried out without prior marriage ties, there is no responsibility that comes from each other. each party, do not think about the consequences that will be accepted, and change partners. Premarital sexual behavior is a problem and a social phenomenon that is often encountered among teenagers. One of the factors that influence premarital sexual behavior is family. The purpose of the study was to determine the effect of family harmony on premarital sexual behavior in adolescents. This research is included in quantitative research with infinite population. The sample in this study amounted to 100 teenagers. Using a purposive sampling technique, with a scale measuring family harmony and premarital sexual behavior in the form of a Likert scale. The results showed that there was an effect of family harmony on premarital sexual behavior with a coefficient value of – 0.581 with a p value of 0.000. Because p value 0.05, it can be interpreted that Family Harmony has a significant effect on Premarital Sexual Behavior with a negative relationship direction.